Introducing Open Access Key - Thomson, Simon (Septentrio Conference Series, 2014)
OAK was founded in 2011 by a former academic publishing executive and a business software developer who encountered first-hand the challenges facing universities and authors with the growth of open access publishing – both Green and Gold. They set about creating a system that dramatically reduced administration and overcame inefficient workflows for all involved. With the establishment of the 'author pays' scholarly publishing model and the increasing trend for open access mandates from research funders, have infrastructure and resources developed sufficiently to support the additional financial and time pressures that participants now face? Individual researchers, their universities and research funders, and the publishers themselves, all have a part to play in processing and managing individual fees. It appears there is a need from all participants in the industry to make provision to encompass the administration of the publication charges required by many open access publishers. Open Access Key (OAK) is a new global company with an innovative and cost-effective solution which could provide value to all parties involved in these transactions. And in addition to financial management, OAK has been built to deliver a wide range of administrative functionality to the users. For example, OAK can feed repositories with the metadata information collected from each article processed through the platform. Automated workflow again reduces the tasks of the authors and administrators allowing resources to be directed towards research. OAK has been built by Norwegian and Danish technology partners using software that delivers tremendous flexibility. At the same time, the company has created an environment that will enable the sharing of best practice models with its customers. The company's size also speeds up decision-making and reactivity. Within an OAK account, for example, there are 'feedback buttons' to enable users to pass on thoughts, requests and general comments directly to the development team. Prior to rolling out the OAK platform to a new customer, the team spends time discussing the needs within each organisation and engineering the system to meet individual specifications.